2018
DOI: 10.1007/s11356-018-2013-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between diurnal temperature range and COPD hospital admissions in Changchun, China

Abstract: Diurnal temperature range (DTR) has been suggested to be an adverse health factor especially related to respiratory and cardiovascular diseases. In the current study, we investigated the association between DTR and chronic obstructive pulmonary disease (COPD) hospital admissions during 2009 to 2012 in northeast city of Changchun, China. Based on generalized additive model (GAM), the effects were expressed as relative risk (RR) values of COPD with 95% confidence intervals (CIs) with each 1 °C increase in DTR. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 56 publications
3
15
0
Order By: Relevance
“…The emergency room visit for exacerbations of COPD was associated with DTR in an ecological study in Taichung city, Taiwan [31]. However, a city-level time series analysis reported that the insignificant relationship between DTR and hospitalization for total COPD patients was found in Changchun, a northeastern city of China [21]. Using data from 21 cities and the method of meta-analysis, we demonstrated that the RR of hospital admissions for exacerbations of COPD was 1.11 (95%CI: 1.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The emergency room visit for exacerbations of COPD was associated with DTR in an ecological study in Taichung city, Taiwan [31]. However, a city-level time series analysis reported that the insignificant relationship between DTR and hospitalization for total COPD patients was found in Changchun, a northeastern city of China [21]. Using data from 21 cities and the method of meta-analysis, we demonstrated that the RR of hospital admissions for exacerbations of COPD was 1.11 (95%CI: 1.…”
Section: Discussionmentioning
confidence: 95%
“…Applicability of those studies may be limited on multi-city or country scale [19]. Moreover, those studies estimated only a single disease of respiratory rather than CRD [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The emergency room visit for exacerbations of COPD was associated with DTR in an ecological study in Taichung city, Taiwan [31]. However, a city-level time series analysis reported that the insigni cant relationship between DTR and hospitalization for total COPD patients was found in Changchun, a northeastern city of China [21]. Using data from 21 cities and the method of meta-analysis, we demonstrated that the RR of hospital admissions for exacerbations of COPD was 1.11 (95%CI: 1.…”
Section: Discussionmentioning
confidence: 95%
“…[12][13][14][15] Ambient mean temperatures may in part account for the public health burden, but the excess public health risk of climate change may also result from temperature variability (TV), a frequent representation of unstable weather. Generally, TV was described by intraday TV as diurnal temperature range (DTR) and interday TV as temperature change between neighboring days (TCN) separately, and the increased risk of COPD was associated with both DTR 16,17 and TCN. 18 Since temperature fluctuation is a continuous process that may last for a few days, considering merely intra-or interday TV may hamper the overall impacts of TV.…”
Section: Introductionmentioning
confidence: 99%
“…20 Although these two indices have been ascertained to be related with mortality or cardiovascular hospitalizations in several studies, [19][20][21][22][23][24] to our best knowledge, relevant evidence on the adverse effect of TV on COPD hospitalization remains limited. Liang et al 16 and Ma et al 17 investigated the effect of DTR within a day on COPD hospitalization. A study in Hong Kong has found that seasonal TV during the whole summer or winter increased COPD hospitalizations among an elderly cohort.…”
Section: Introductionmentioning
confidence: 99%